Communication For Chinese Culinary Culture at China Town in Bangkok - Juntao, Huang; Buranadechachai , Sukanya; Boonpiam, Sakdina (Journal of Dhamma for Life, 2025)
This dissertation examines the communication strategies employed to disseminate Chinese culinary culture in Bangkok’s Chinatown (Yaowarat) and investigates their impact on cross-cultural exchange, cultural identity formation, and tourism development. Grounded in theories of cross-cultural communication, soft power, and digital media dissemination, the study constructs an analytical framework that links communication sources, message construction, distribution channels, and audience reception in a multicultural urban context. Utilizing a mixed-methods approach, quantitative surveys and qualitative interviews were conducted with local Thai residents, Chinese tourists, international visitors, and key stakeholders such as restaurant owners and cultural promoters in Yaowarat. Statistical analysis of the survey data revealed significant differences in perceptions of Chinese culinary culture, underscoring the influential role of digital media in shaping consumer behavior. In-depth interviews further highlighted how culinary enterprises strategically adapt menus, adjust flavor profiles, and integrate culturally resonant decor elements to balance traditional Chinese values with local Thai preferences. Findings indicate that the integration of traditional communication practices with innovative digital platforms significantly enhances the dissemination of Chinese culinary culture. Social media platforms, in particular, serve as critical conduits for rapid cultural exchange, allowing for real-time consumer interaction and feedback that continuously refine communication strategies. Such hybrid trategies not only bolster cultural transmission but also enhance China’s international image and soft power by positioning Yaowarat as a vibrant hub of cultural convergence. The study extends existing cross-cultural communication models by incorporating the dynamic influence of digital media on cultural dissemination. It offers both theoretical and practical contributions, suggesting that integrated online and offline communication strategies can optimize cultural promotion and tourism development. The research recommends that stakeholders invest in advanced data analytics and digital marketing techniques to monitor consumer behavior and adapt communication practices in an ever-evolving digital landscape.